Nanopatterning of GeTe phase change films via heated-probe lithography. Issue 25 (19th June 2017) - Podpirka, Adrian; Lee, Woo-Kyung; Ziegler, Jed I.; Brintlinger, Todd H.; Felts, Jonathan R.; Simpkins, Blake S.; Bassim, Nabil D.; Laracuente, Arnaldo R.; Sheehan, Paul E.; Ruppalt, Laura B.
Abstract : Nanoscale lithography of GeTe phase change films is demonstrated using a heated-probe AFM. Submicron features with dramatic electronic, topographic, and optical contrast are generated, opening a new approach to nano-(opto)electronic device fabrication. Abstract : The crystallization of amorphous germanium telluride (GeTe) thin films is controlled with nanoscale resolution using the heat from a thermal AFM probe. The dramatic differences between the amorphous and crystalline GeTe phases yield embedded nanoscale features with strong topographic, electronic, and optical contrast. The flexibility of scanning probe lithography enables the width and depth of the features, as well as the extent of their crystallization, to be controlled by varying probe temperature and write speed. Together, these technologies suggest a new approach to nanoelectronic and opto-electronic device fabrication.